2008
DOI: 10.1029/2007jd008623
|View full text |Cite
|
Sign up to set email alerts
|

Midweek increase in U.S. summer rain and storm heights suggests air pollution invigorates rainstorms

Abstract: [1] Tropical Rainfall Measuring Mission (TRMM) satellite estimates of summertime rainfall over the southeast U.S. are found on average to be significantly higher during the middle of the work week than on weekends, attributable to a midweek intensification of afternoon storms and an increase in area with detectable rain. TRMM radar data show a significant midweek increase in the echo-top heights reached by afternoon storms. Weekly variations in model-reanalysis wind patterns over the region are consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
244
2
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 214 publications
(269 citation statements)
references
References 78 publications
(104 reference statements)
21
244
2
2
Order By: Relevance
“…Our results showed that the previously reported [1][2][3][4][5] enhancement in the lightning activity of thunderstorms as the concentration of aerosols increases is not universal. Under conditions of ample amounts of water vapor, increasing the aerosol concentration resulted in the formation of more small cloud droplets, reducing the collision coalescence efficiency of the cloud droplets and suppressing the warm rain process.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our results showed that the previously reported [1][2][3][4][5] enhancement in the lightning activity of thunderstorms as the concentration of aerosols increases is not universal. Under conditions of ample amounts of water vapor, increasing the aerosol concentration resulted in the formation of more small cloud droplets, reducing the collision coalescence efficiency of the cloud droplets and suppressing the warm rain process.…”
Section: Discussionsupporting
confidence: 72%
“…At the lowest water vapor content (85% of the baseline sounding), the mean flash rate remained almost constant with increasing aerosol concentrations. Previous studies [1][2][3][4] have also indicated that an increase in the concentration of aerosol particles enhances the intensity of electrical activity. However, this does not apply to all thunderstorms under different conditions, and there are still uncertainties in the effects of aerosol on thunderstorm microphysics and electrification processes.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then others [e.g., Lin et al, 2006;Ten Hoeve et al, 2012] have also found evidence of higher cloud tops, enhanced heavy precipitation, and increased ice amounts in the same region. Similar evidence has also been found for convective invigoration (e.g., increased cloud tops, more frequent lightning, and heavier precipitation events) in polluted environments over the North Atlantic Ocean [Koren et al, 2005], in the southeast United States [Bell et al, 2008], and in China [Wang et al, 2011]. Wang et al [2009] analyzed both observational and modeling data and found evidence that smoke from biomass burning in Central America may lead to an enhancement of severe weather in the south central United States.…”
Section: Introductionmentioning
confidence: 75%
“…The aerosols were found even to affect the potential of deep convective clouds to produce large hail and tornadoes, where clouds with added pollution aerosols become potentially more damaging (Rosenfeld and Bell, 2011 and references therein). The impact of aerosols on cloud invigoration and the vertical distribution of latent heating can also modulate regional and large scale circulation systems, as observed by Bell et al (2008) and simulated by Fan et al (2012).…”
Section: Ways By Which Aerosols Affect Cloud Microphysical Precipitamentioning
confidence: 99%